Sebaran Ukuran, Hubungan Panjang-Berat Dan Faktor Kondisi Ikan Pantau Janggut (Esomus metallicus AHL) Di Sungai Tenayan Dan Tapung Mati, Riau - Pulungan, Chaidir P.; Zakaria, Indra Junaidi; ', Sukendi; ', Mansyurdin (Fakultas Perikanan dan Kelautan Universitas Riau, 2012)
The research about length frekuency distribution, length-weight relationshipand factor condition stripped flying barb in Tenayan and Tapung Mati River, RiauProvince have been conducted from May 2010 until April 2011. Fishes were caughtby floating net (2 x 5 m) and scoopnet (diameter 0,5 m). The fish samples werecollected every month, and fish collecting based on sensus method. The researchpurpose to know the biggest length frekuency distribution of stripped flying barb inthe nature population. Growth pattern and condition factor of stripped flying barb.Result shown that the population of stripped flying barb is dominate by lengthfrekuency distribution 41 – 50 mm, growth pattern of fish was allometric negativeand value condition factor of the female is the biggest than the male fishes.